An Analysis of Needs Response to the Development of E-Module Material Elasticity and Hooke Law at Lebong Regency High School - Erlina, Rita; Risdianto, Eko; Hamdani, Dedy; Fathurrochman, Irwan; Efendi, Rusdi; Prananosa, Ahmad Gawdy (Graduate Program Magister Manajemen Pendidikan, 2022)
The purpose of this study is to analyze the response of needs to the development of E-modules material elasticity and hooke law in Lebong Regency high school. This research is part of the R n D research method but is only limited to the needs analysis stage, the sampling technique used is pusposive sampling with data samples in this study, namely 201 students of grade XI IPA and 5 physics teachers in 3 high schools. The data collection techniques used are interviews, questionnaires and observations. The instrument used in this research is an e-module development needs questionnaire sheet for students and teachers. Test results showed that the instrument used was valid and reliable. The results also mentioned that students and teachers at high school in Lebong Regency urgently need the development of E-modules of elasticity and hooke law. With the results obtained from the responses of teachers and students namely strongly agree. Therefore, from these results, researchers hope to contribute to educational practitioners in order to develop teaching materials in the form of E-modules of elasticity and hooke law for students.